2008
DOI: 10.1128/aem.02863-07
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Hidden Secondary Metabolome of Myxococcus xanthus : a Study of Intraspecific Diversity

Abstract: As a monophyletic group, the myxobacteria are known to produce a broad spectrum of secondary metabolites. However, the degree of metabolic diversity that can be found within a single species remains unexplored. The model species Myxococcus xanthus produces several metabolites also present in other myxobacterial species, but only one compound unique to M. xanthus has been found to date. Here, we compare the metabolite profiles of 98 M. xanthus strains that originate from 78 locations worldwide and include 20 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
123
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(133 citation statements)
references
References 31 publications
1
123
0
3
Order By: Relevance
“…A high level of phenotypic and genetic diversity has been documented among cm-scale M. xanthus isolates (7,36,(42)(43)(44)(45), despite the fact that genetic diversity at this scale was found to be much lower than at only slightly larger sampling scales (8). For example, genetically similar centimeter-scale isolates were found to show extremely divergent competitive abilities during fruiting body development in forcibly mixed pairings (36).…”
mentioning
confidence: 99%
“…A high level of phenotypic and genetic diversity has been documented among cm-scale M. xanthus isolates (7,36,(42)(43)(44)(45), despite the fact that genetic diversity at this scale was found to be much lower than at only slightly larger sampling scales (8). For example, genetically similar centimeter-scale isolates were found to show extremely divergent competitive abilities during fruiting body development in forcibly mixed pairings (36).…”
mentioning
confidence: 99%
“…In addition, the percentage of extracts that caused clear zones due to inhibited spore germination of three or four fungi was 15−44% for cellulolytic but only 0− 6% for bacteriolytic myxobacteria. Although most research on bioactivity has been conducted on bacteriolytic myxobacteria (Bull et al, 2002;Chung et al, 2008;Kim et al, 1998;Kim et al, 2003b;Krug et al, 2008;Kim and Yun, 2011), more cellulolytic myxobacteria should be studied because they have superior antifungal activity to bacteriolytic myxobacteria. Among the five tested phytopathogens, B. cinerea was the best controlled with 455 myxobacterial extracts.…”
Section: Discussionmentioning
confidence: 99%
“…(Ahn and Kim, 2002;Bull et al, 2002;Chung et al, 2008;Kim and Yun, 2011;Kim et al, 1998;Kim et al, 2003b;Krug et al, 2008), although the antifungal activity of S. cellulosum, a cellulolytic myxobacterium, against several phytopathogenic fungi has been examined in Germany (Reichenbach and Höfle, 1994). Soraphen and epothilone are two natural products of S. cellulosum, and soraphen in particular is an antifungal compound.…”
mentioning
confidence: 99%
“…Myxobacteria are a rich source of bioactive secondary metabolites that are not found in other antagonists such as pseudomonads and Bacillus spp. and are being evaluated as a source of novel compounds (Bull et al, 2002;Dawid, 2000;Gaspari et al, 2005;Gerth et al, 2003;Krug et al, 2008;Reichenbach, 2001). In studies over more than 25 years, about 80 basic structures and 350 variants have been identified.…”
mentioning
confidence: 99%
“…The bacteriolytic myxobacteria produce the agriculturally important antibiotic, pyrrolnitrin. The genera Myxococcus, Corallococcus, Cystobacter, Archangium, and Stigmatella are bacteriolytic myxobacteria and are rich sources of bioactive metabolites including aurachin, corallopyronin, crocacin, myxalamid, myxochelin, myxothiazol, myxovirescin, pyrrolnitrin, saframycin, and stigmatellin (Bartlett et al, 2002;Dawid, 2000;Kim et al, 2003;Krug et al, 2008;Reichenbach, 2001;Wang and Tao, 2009).…”
mentioning
confidence: 99%